Clinicopathological features of pilomatricoma cases: Analysis of 21 cases - Ghartimagar, D; Ghosh, A; Gautam, K; Thapa, S; Shrestha, SR; Narasimhan, R (Journal of Pathology of Nepal, 2014)
Background: Pilomatricoma is a slow-growing, asymptomatic tumour originating from outer sheath cells of hair follicle. In this study, we describe the clinical presentation and histopathological features of pilomatricoma. Materials and Methods: This was a hospital based retrospective study carried out in all patients who were diagnosed as pilomatricoma over a period of January 2001 to December 2013. The study was done in department of pathology, Manipal Teaching Hospital, Nepal. Results: A total of 21 cases of pilomatricoma were reported with age range of 9-53 years (mean age 23.7) and male female ratio of 1:1.1. The most common site of occurrence was neck and preauricular region. The size of the tumour ranged from 0.3 to 4.7cm with a mean of 1.2cm. Multiple occurrences were seen in 3 patients and ossifying pilomarticoma was seen in 4 cases. Conclusion: Pilomatricoma is a benign skin neoplasm of hair follicle matrix cells. Calcification is a common finding while dystrophic ossification also can occur in the tumour. Histopathology gives the definite diagnosis as fine needle aspiration cytology and clinical impression may be misleading. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10293 Journal of Pathology of Nepal (2014) Vol. 4, 530-533